Self-efficacy and Drug-seeking Behaviors in High School Students in Southern Iran - Fatemeh Sadat Hossaini; Vahid Kohpeima Jahromi; Vahid Rahmanian; Nader Sharifi (Shiraz University of Medical Sciences, 2022)
Background: The tendency to the use of drugs is a daily increase, especially among adolescents. We conducted the present study to investigate the role of self-efficacy in predicting drug-seeking behaviors among high school students in Jahrom, Fars province, Iran. Methods: This cross-sectional study was performed on high school students in Jahrom, Fars province, Iran in 2020. The sample size was estimated to be 405 people who were chosen using multi-stage cluster sampling. The data collection tools here included demographic information questionnaire, Iranian Addiction Potential Scale, and self-efficacy questionnaire Children Scale. Data analysis was performed with SPSS version 21 using descriptive statistics and Pearson's correlation coefficient, Independent t-test, One-way ANOVA, and Linear regression. Results: There was a significant inverse correlation between self-efficacy and drug-seeking behaviors (r=-598, p <0.001). Additionally, the results revealed a relationship between grade, father's job, mother's education, and smoking history in friends and parents with self-efficacy (P=0.002, P=0.012, P=0.004, P=0.006, P=0.005, respectively) and drug-seeking behaviors (p <0.001). Father's job, friends' smoking history, and self-efficacy were significant factors inversely associated with drug-seeking behaviors (P=0.003, p <0.001, p <0.001, respectively). Conclusion: High levels of self-efficacy of students and educated families can play a protective role against drugs use. Further focus on prevention, especially on capacity building and the empowerment of young people can reduce the tendency to use drugs.